Analysis for a solar stripper design for carbon capture under transient conditions. (February 2021) - Milani, Dia; Luu, Minh Tri; Nelson, Scott; Mohsin, Hanan; Liu, Yiqing; Puxty, Graeme; McNaughton, Robbie; Abbas, Ali
Highlights: The typical stripper in the PCC is replaced by an innovative solar stripper (So-St). The conceptual design for direct solvent regeneration in the solar field is analysed. A design protocol to calculate So-St segments and modules layout is developed. The length and diameter of subsequent segments to the overall design is optimized. The process control for the pressure drop and enhanced heat transfer is maintained. Abstract: This paper presents an advanced thermodynamic analysis to design a solar stripper (So-St) field to replace the conventional desorption unit in a post-combustion carbon capture (PCC) plant. By eliminating the large, complex, and costly stripper, a solar collector field (SCF) consisting of a number of So-St arrays is sized to directly release the CO2 gas from the rich solvent under transient conditions. In this study, a design protocol has been developed to address the key design challenges for the evolving two-phase flow in the solar receiver tube analysing the instantaneous flow regime, pressure drop, and vapour molar fraction (VMF) to enhance the heat transfer. This design protocol optimizes the physical properties of the So-St components and eventually leads to the whole So-St field sizing based on the nominal capture capacity. A case-study is demonstrated to capture 1.5M tonneCO2 /y from a representative 660 MWe coal-fired power plant in Sydney/Australia. It is found that 22 rich solvent loops that each consists of an array of 6 parallel So-St modules, where each module consists of 6 segments in series is needed. The length/diameter of these So-St segments/modules are optimized for this case-study, and the design procedures are clarified and simplified which can be easily applied for other case-studies. Techno-economic validation of this novel So-St technology is an essential step-forward to fully solarize and autonomies carbon capture industry.